THE IMPLEMENTATION OF REWARD AND PUNISHMENT IN ENGLISH LEARNING FOR 10TH GRADE STUDENTS AT SMKN 1 JABON - Lillah, Mar'ah Chaninah; Aisyah, Siti; Musyarofah, Lailatul (PROJECT (Professional Journal of English Education), 2024)
English is one of the main subjects that must be mastered by students to keep up with the development of science and technology. To anticipate the development of science and technology, it is necessary to improve English language skills in vocational high school students. This paper presents a descriptive qualitative study on the implementation of reward and punishment in English learning in a vocational high school, namely SMKN 1 Jabon. The researchers used observation and questionnaires as instruments to collect data. The participants in this study were an English teacher and 36 students. The researchers implemented three types of rewards and one type of punishment: social reward, token reward, material reward, and presentation punishment. The results of the questionnaire indicate that the students have agreed and accepted well the rewards and punishments implemented by the teacher. They feel happy with the praise given by the teacher with good words such as good job, amazing, great, and happy when given gifts, congratulations, and extra points as rewards.  Therefore, they become enthusiastic and compete in learning English. In addition, they also agree with the punishments given to students, such as being given advice, and warnings, standing in front of the class, cleaning the class, running around the field, and others. Therefore, they are discouraged and do not want to repeat their mistakes.